Artificial Intelligence (AI) in Palliative Care: Ethical Challenges - Karatzanou, Natalia (Bioethica, 2025)
Palliative Care (PC), which has recently become a more prominent field in healthcare, focuses on providing patients quality of life, relief from pain and other symptoms of serious illnesses, regardless of the diagnosis or stage of the disease. Even though several studies have reported the development of Artificial Intelligence (AI) in medicine, AI in the field of PC is still in early progress. The application of AI technologies in PC raises many ethical challenges which this paper will attempt to highlight. To achieve this, a literature review was conducted, scientific studies were gathered and were critically examined. It was observed that current AI applications in PC include Mortality risk prediction, Data annotation and Morbidity prediction. Ethical dilemmas and the legal framework will be investigated to emphasize the rights of patients, as well as the responsibilities and obligations healthcare professionals carry. Furthermore, directions for trustworthy AI in PC will be proposed. Finally, since PC requires a close doctor-patient relationship, healthcare professionals should focus on developing AI algorithms that align with the patients’ needs and the goals of PC.